Макетний зразок комп'ютеризованого вимірювача параметрів мікроклімату промислових теплиць - Вовна, Олександр Володимирович; Лактіонов, Іван Сергійович; Зорі, Анатолій Анатолійович (НТУ "ХПІ", 2017)
У статті шляхом аналізу регламентованих вимог щодо режимів зростання рослин на захищених ґрунтах та існуючих рішень побудови систем автоматичного управління технологічними процесами промислових теплиць обґрунтовано структурну схему комп'ютеризованого вимірювача параметрів мікроклімату теплиць. Розроблено апаратно-програмну реалізацію макетного зразка вимірювача. Проведено лабораторні випробування розробленого засобу вимірювання. Визначено пріоритетні напрямки подальших досліджень вимірювача з метою підвищення ефективності вітчизняних аграрних підприємств із захищеними ґрунтами.

The deep analysis of the regulated requirements for the plant growth regimes on the protected soils has been carried out in this paper. Also, the construction of the existing automatic control systems of the industrial greenhouses technological process have been analyzed. The block diagram of the greenhouses microclimate parameters computerized meter has been substantiated. The component base of the computerized meter has been defined. The hardware and software component of the computerized meter model sample have been technically implemented. Structural organization of the computerized meter of greenhouse microclimate parameters has been investigated based on study and synthesis of its subsystems functional maintenance. It provides comprehensive moisture, acidity, temperature, CO₂ concentration, electrical conductivity of the irrigation water and etc. measurements with destabilizing effects compensation which allows its operation as a part of the industrial greenhouse automation complex. The network technologies are included in the developed meter. Designed meter has the function of the measured parameters database creating. Laboratory tests of the established measurement mean have been conducted. Priority areas for further meter research have been identified, which will allow to increase the efficiency of Ukrainian agricultural enterprises with protected soils in the future.
The computerized meter model sample of the industrial greenhouses microclimate parameters
Keywords: температура; вологість; фотосинтетична активна радіація; ФАР; рослини; moisture; temperature